Automated Database Schema Matching Engine - Sailan, Maha (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Database Schema Matching is a process which intakes multiple schema as an entry and yields back a mapping that classifies a similar component in these schemas. This process is mostly used to locate and identify semantically related-target. With this method or process it eases the finding and matching of divergent and randomly scattered data sets. It is one valuable tool for data processing and schema integration. Researches shows that various methods for schema matching based on different schema level matcher and classification criteria are proposed in order to find the most similar attributes and element in the schemas. Schema matching is classified into two approaches; Individual Match Approach and Combining Matchers Approach. In this thesis the individual match approach is used, which considers the schema level that is linguistic based. Past studies exhibited several methodologies to make the matching process in schema matching partially and fully automated, while in this thesis Convolutional Neural Network (CNN) methodology is proposed to implement an automated database schema matching engine with the aid of cosine similarity algorithm and Jaro Winkler algorithm. One of the powerful characteristics of the proposed methodology is that, it can be automated hence, less time is required to carry a particular task and more efficient if the task is more complex and if it is a larger scale task. The proposed methodology showed a very satisfactory result. The purpose of this thesis is to implement an automated database schema matching engine in addition to research and study the techniques and methodologies that is used for schema matching. Keywords: Schema Matching, Individual Match, Multiple Matchers, Convolutional Neural Network

ÖZ:Veritabanı Şeması eşleştirme, birden çok şemayı bir girdi olarak alan ve bu şemalarda benzer bir bileşeni sınıflandıran bir eşlemeyi üreten bir süreçtir. Bu işlem çoğunlukla anlamsal olarak ilişkili hedefi bulmak ve tanımlamak için kullanılır. Bu yöntem veya işlem sayesinde farklı ve rastgele dağılmış veri kümelerinin bulunması ve eşleştirilmesi kolaylaşır. Veri işleme ve şema birleştirilmesi için değerli bir araçtır. Araştırmalar, şemalarda en benzer özellikleri ve öğeleri bulmak için farklı seviyedeki şema eşleştiricisi ve sınıflandırma kriterlerine dayalı olarak şema eşleştirmesi için çeşitli yöntemlerin önerildiğini göstermektedir. Şema eşleştirme iki yaklaşım olarak sınıflandırılır; Bireysel Eşleşme Yaklaşımı ve Eşleştirici Birleşmesi Yaklaşımı. Bu tezde, dil temelli şema düzeyini dikkate alan bireysel eşleşme yaklaşımı kullanılmaktadır. Geçmiş çalışmalar şemada eşleştirme işlemini kısmen ve tamamen otomatik hale getirmek için çeşitli metodolojiler sergilerken, bu tezde Sarmallı Sinir Ağı (CNN) metodolojisi, kosinüs benzerlik algoritması ve Jaro winkler algoritması yardımıyla otomatik bir veritabanı şeması eşleştirme motorunun uygulanmasını önerir. Önerilen metodolojinin en önemli özelliklerinden biri, otomatikleştirilebileceğinden dolayı, belirli bir görevi yerine getirmek için daha az zamana ihtiyaç duyulması ve görev daha karmaşıksa ve daha büyük ölçekli bir görev ise daha verimli olmasıdır. Önerilen metodoloji oldukça tatmin edici sonuçlar göstermiştir. Bu tezin amacı, şema eşleştirme için kullanılan teknikleri ve metodolojileri araştırmaya ve incelemeye ek olarak otomatik bir veritabanı şema eşleştirme motorunu uygulamaktır. Anahtar Kelimeler: Şema Eşleştirme, Bireysel Eşleme, Çoklu Eşleştiriciler, Sarmallı Sinir Ağı.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2020. Supervisor: Assoc. Prof. Dr. Duygu Çelik Ertuğrul.
Keywords: Data in computer systems; Data integration (Computer science); Schema matching; Schema Matching; Individual Match; Multiple Matchers; Convolutional Neural Network